Culture results from wound biopsy versus wound swab: does it matter for the assessment of wound infection?. (May 2019) - Haalboom, M.; Blokhuis-Arkes, M.H.E.; Beuk, R.J.; Meerwaldt, R.; Klont, R.; Schijffelen, M.J.; Bowler, P.B.; Burnet, M.; Sigl, E.; van der Palen, J.A.M.
Abstract: Objectives: The aim of this study was to determine whether assessment of wound infection differs when culture results from wound biopsy versus wound swab are available in clinical practice. Methods: For 180 eligible patients, a swab and biopsy were taken from one wound during a regular appointment at a wound care facility in eastern Netherlands. Culture results from both methods were supplemented with clinical information and provided to a panel of six experts who independently assessed each wound as infect or not, separately for swab and biopsy. Assessments for biopsy and swab were compared for the complete expert panel, and for individual experts. Results: The complete expert panel provided the same wound assessment based on (clinical information and) culture results from wound biopsy and wound swab in 158 of 180 wounds (87.8%, kappa 0.67). For individual experts, agreement between biopsy and swab varied between 77% and 96%. However, there were substantial differences between experts: the same assessment was provided in 62 (34.4%) to 76 (42.2%) wounds for swab and biopsy respectively. Conclusions: Assessment of infection does not significantly differ when culture results from swabs or biopsies are available. The substantial variability between individual experts indicates non-uniformity in the way wounds are assessed. This complicates accurate detection of infection and comparability between studies using assessment of infection as reference standard. Graphical abstract: Image 1